2009
DOI: 10.1016/s1472-6483(10)60070-3
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and ObRa/MEK signalling in mouse oocyte maturation and preimplantation embryo development

Abstract: Recent studies indicate that LH stimulates production of ovarian paracrine factors that induce meiosis of the oocyte. DNA microarray analyses of ovarian transcripts were performed in mice and major increases of a short isoform of leptin receptor, ObRa, were identified by the preovulatory LH/human chorionic gonadotrophin (HCG) surge. In oocytes, the level of ObRa transcripts was increased shortly after HCG stimulation, whereas the level of ObRb transcripts was not changed. Leptin was produced by cumulus, granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
1
15
0
1
Order By: Relevance
“…Based on previous studies suggesting that media supplementation of certain autocrine/paracrine factors can enhance oocyte maturation and early embryo development (54,55), our final objective was to determine whether the addition of defined growth factors to culture media had any effects on the expression of epigenetic regulators in human embryos by Q-PCR (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies suggesting that media supplementation of certain autocrine/paracrine factors can enhance oocyte maturation and early embryo development (54,55), our final objective was to determine whether the addition of defined growth factors to culture media had any effects on the expression of epigenetic regulators in human embryos by Q-PCR (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…1B). For this purpose, we evaluated DNMT and histone-modifying enzyme expression in embryos cultured with a growth factor cocktail containing brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-I), epidermal growth factor (EGF), granulocyte macrophage colony-stimulating factor (GM-CSF), basic fibroblast growth factor (bFGF)/FGF2 and glial cell line-derived neurotrophic factor (GDNF), which were selected based on the aforementioned studies (54,55) as well as the confirmation of their corresponding receptor expression in human oocytes (56). Although similar blastocyst formation rates (∼30%) were observed with human zygotes cultured in the absence or presence of the growth factor cocktail, comparison of gene expression between the two groups revealed that media supplementation induced changes in DNMT and histone-modifying enzyme expression beginning at the eight-cell stage (Supplementary Material, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we generated the hypothesis that the lipid accumulation in the canine endometrial epithelium is not a sign of degeneration but has a potential function during implantation, foetal development and placentation. An important signalling cytokine involved in implantation and embryo development in mammals is leptin (Gonzalez et al, 2000;Hoggard et al, 2001;Linnemann et al, 2001;Sagawa et al, 2002;Kawamura et al, 2003;Craig et al, 2005;Kim et al, 2006;Schmidt et al, 2008;Ye et al, 2009). Leptin is one of the best-characterized adipokines in domestic animal species, playing a well-known important role in satiety, adiposity and metabolism [for review see Radin et al (2009))].…”
Section: Introductionmentioning
confidence: 99%
“…Leptin is one of the best-characterized adipokines in domestic animal species, playing a well-known important role in satiety, adiposity and metabolism [for review see Radin et al (2009))]. However, functions in reproduction especially in pre-implantation and embryo development have also been described for leptin in humans and animals in vivo and in vitro (Clarke and Henry, 1999;Harris, 2000;Chehab et al, 2002;Moschos et al, 2002;Budak et al, 2006;Ye et al, 2009;Arias-Alvarez et al, 2011;Dos Santos et al, 2012). Therefore, in this study, we were interested in potential leptin expression in the canine endometrium and especially in the fEECs representing both, reproductive tissue cells and due to the lipid accumulations potential cytokine-producing cells.…”
Section: Introductionmentioning
confidence: 99%
“…Only the long isoform (OBRb) was initially considered to be a functional receptor because it contains all the intracellular domains required for effective signalling through activation of both the JAK/STAT and MAPK pathways (Tartaglia et al 1995, Bjørbaek et al 1997. However, OBRa, one of the short isoforms, also has different signalling capacities, especially through the MAPK pathway (Bjørbaek et al 1997, Murakami et al 1997, Caü zac et al 2003, Ye et al 2009). As OBRb does not have intrinsic enzymatic activity, its signalling cascade occurs via JAK2, which undergoes autophosphorylation and simultaneously induces phosphorylation in other tyrosine residues in the cytoplasmic region of the leptin receptor, which, in turn, allows the association of STAT proteins.…”
Section: Introductionmentioning
confidence: 99%